Geologi Untuk Mengetahui Satuan dan Sebaran Jenis Litologi Endapan Material Lepas Sungai Daerah Sungai “KLG” - Afifah, Rohima Sera (INFO-TEKNIK, 2023)
The Alluvium Formation of the Upper Fluvial "KLG" area is a fluvial alluvial deposit in the form of pebbles - granule of andesite and basalt grain size. The lithology unit is a Fluvial Alluvial that includes the Fluvial Plain and Fluvial Body. The diversity of grain sizes is due to the influence of the Sedimentological process. The sedimentological process begins with the rocks being and or being uplifted to the surface undergoing weathering, transport time / transport distance, resistance and crystal shape. The type of fluvial sediment material is divided into 2 (two) parts, namely: 1) the upstream part of the fluvial, generally in the form of coarse-sized alluvial deposits including the size of boulders, pebbles, granule, and sand, 2) the downstream part of the fluvial, generally in the form of finer-sized deposits. The research focused on geological studies with a lithological unit approach to the Upper Fluvial "KLG" area. The research aimed to determine the lithological unit of the Upper Fluvial "KLG" area and the distribution of grain size of unconsolidated sediment in the Upper Fluvial "KLG" of study area. The research method was carried out with 3 (three) methods, namely: a) Descriptive Method, by means of literature study, b) Survey Method, by means of factual information in the research area, with the stages of Field Observation including: Observation of geological appearances including outcrops, recording, sampling and recording field data in the Upper Fluvial "KLG", c) Analysis Methods include: Petrology and Sieve Analysis. Research results showed that The Geomorpholgy was Fluvial Alluvial plain. The Formation area was Alluvial Formation with unconsolidated sediment fluvial lithology. The grain sizes of Unconsolidated sediment were boulders, pebbles, granule and sand. Keywords: Alluvial Formation, Fluvial, Unconsolidated Sediment